(untitled) (Revista Paradigma, 2020)
The present research deals with translocal citizenship as a possibility of reception, acceptance and recognition of excluded groups, such as environmental refugees, people forced to travel due to the occurrence of natural disasters. In this sense, the objective is to describe, through the deductive method, the technique of bibliographic research and historical procedure, the challenges faced by environmental refugees, since they are denied recognition and international legal protection. From this, study translocal citizenship as a human and just alternative to recognize, accept and respect all life forms, which includes preserving the environment and multicultural society as a whole. Translocal citizenship, which mediates different people and cultures, aims to guarantee each and every one the human rights, human dignity and cultural freedom at local, national and global level, crossing state borders. As such, it contributes to the recognition, respect and acceptance of excluded people as environmental refugees, as well as to focus on the preservation of all forms of life - human and ecological.